Gains from Improved Technology Adoption in Disadvantaged Regions: Evidences from Bundelkhand Region - SAXENA, RAKA; KANWAL, VINITA; KHAN, MOHDARSHAD; VERMA, SUMAN; B, GURURAJ (The Indian Journal of Agricultural Sciences, 2022)
The study explored the status and determinants of technology adoption in terms of shifting towards high yielding varieties, micro-irrigation and mechanisation in Bundelkhand zone. The study is based on a field survey conducted in the Jhansi district of Bundelkhand region in 2018–19. Bundelkhand is a water scarce area of the country and needs policy interventions in the form of efficient water utilization and enhanced production. The results indicate that despite least adoption of sprinkler in the region, micro-irrigation has resulted in water use conservation and improved yields in comparison to conventional irrigation method. The findings revealed that age, income from cultivation, possession of MGNREGA job card and membership of any local and village level organization had a considerable impact on the decision to adopt improved agricultural varieties and micro-irrigation implying that the security nets provided in any form motivates the households to adopt improved technology. Size of operated land, income from non-agricultural activities and possession of Kisan Credit Card are the significant factors in case of farm mechanisation.